2020
DOI: 10.1088/2053-1591/ab6e2f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of silicon nanoparticles by laser ablation at low fluences in water and ethanol

Abstract: Colloidal silicon nanoparticles (Si-nc) where synthesized by laser ablation of a solid Si target in water and ethanol. The target was immersed in a vessel containing the solvent and irradiated during 5 and 10 min at different fluences: 0.530, 0.608, 0.687 J cm −2 . Ablation was carried out using a laser wavelength of 1064 nm. The obtained colloidal nanoparticles were irradiated after the synthesis to evaluate if laser fragmentation could be produced. In addition, a series of nanoparticles using ethanol as liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…The laser ablation of silicon or silicon nanostructures in liquids opens up a promising way to manufacture almost ready-to-use suspensions of SiNPs of the desired size free of any chemical impurities [40][41][42]. For example, SiNPs of mean size of 20-30 nm formed by the laser ablation of porous silicon were employed as agents for photohyperthermia: irradiation of the SiNP aqueous suspension (0.4 mg/mL) containing unicellular Paramecium caudatum organisms by continuous-wave laser radiation with the intensity of 25 kW/cm 2 at a wavelength of 808 nm was found to result in temperature rise up to 20 • C and death of the living cells [43].…”
Section: Introductionmentioning
confidence: 99%
“…The laser ablation of silicon or silicon nanostructures in liquids opens up a promising way to manufacture almost ready-to-use suspensions of SiNPs of the desired size free of any chemical impurities [40][41][42]. For example, SiNPs of mean size of 20-30 nm formed by the laser ablation of porous silicon were employed as agents for photohyperthermia: irradiation of the SiNP aqueous suspension (0.4 mg/mL) containing unicellular Paramecium caudatum organisms by continuous-wave laser radiation with the intensity of 25 kW/cm 2 at a wavelength of 808 nm was found to result in temperature rise up to 20 • C and death of the living cells [43].…”
Section: Introductionmentioning
confidence: 99%
“…1a) shows the UV-Vis transmittance spectrum of the colloid. Notice that there is an absorption edge near 600 nm, which is in the visible range of the spectrum, being an indicative of band gap widening due to quantum effects arising from the size reduction [11].…”
Section: Resultsmentioning
confidence: 99%
“…Different approaches have been carried out to fabricate Si nanoparticles, however, the laser ablation of a solid target immersed in a liquid, has shown to be an excellent alternative to fabricate colloidal Si nanoparticles [9,[11][12][13][14][15][16][17] due to its ability to produce hazardous waste free suspensions and nanoparticles with low size polydispersity [18]. As compared to chemical routes for the synthesis of nanoparticles in which chemical precursors, stabilizers and surfactants are used, the laser ablation of solids in liquids offers the advantage of obtaining pure nanoparticles without generation of residues arising from all chemicals used for reactions [19][20][21], avoiding the need for washing procedures for the final products.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has examined the potential effects of adding water or other liquids to laser ablation to confine the plasma expansion. According to reports, the containment of plasma expansion by water increases the shock pressure impact [11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they applied the fragmentation process to reduce the size of silicon NPs. They found that using a 1064 nm laser wavelength decreased the size of Si nanoparticles [11]. M. Taheri et al used PLAL in two stages to synthesize oxide silicon nanoparticles by applying an Nd:YAG laser with a 1064nm wavelength, a 13 ns pulse duration, and a 10 Hz pulse rate.…”
Section: Introductionmentioning
confidence: 99%